Bromocriptine in Parkinson's disease: a study of cardiovascular effects. Issue 5 (May 1981) - Quinn, N; Illas, A; Lhermitte, F; Agid, Y
Abstract : Blood pressure and pulse rate were studied in 20 Parkinsonian patients on no treatment, and during treatment with bromocriptine (mean dosage 148 mg/day) as the sole anti-Parkinsonian therapy. The drug was shown to reduce erect systolic and diastolic and supine systolic blood pressure and to increase erect pulse rate, in a predictable dose-dependent manner. The occurrence of episodes of significant postural hypotension was less predictable and was a transitory phenomenon in all patients. Peripheral dopamine receptor blockade with domperidone did not alter the findings, suggesting that the principal mechanism for these cardiovascular effects is a central dopaminergic one.